(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
1-The difference of the schools of jurisprudence regarding the assumption of the position of the judiciary of women into four sayings The first saying: It is not permissible for a woman to follow the judiciary at all, and her guardianship is null, and her spending is not enforceable, which is the view of the majority of the Maliki, Shafi’i, Hanbali and Zafar Ibn al-Hudhail from the Hanafi The second saying: It is permissible for a woman to follow the judiciary absolutely. The third saying: It is permissible for a woman to follow the judiciary absolutely, with no limits or qisas, and her guardianship is valid and her rulings are valid as far as her testimony is accepted, and to this saying went the Hanafis, and Ibn al-Qasim of the Malikis The fourth saying: Permissibility is absolutely permissible in case of necessity, and if it is found necessary, then necessities permit prohibitions, so it is permissible for a woman to assume the judiciary and implement her rulings Lest the interests of the people be disrupted; And to him went the Shafi’is 2-The preponderance of the opinion that a woman should assume the judiciary within certain limits, such as “the judiciary for women and other matters related to women that men do not see” in order to achieve the interest, and in line with the flexibility of Islam, and the requirements of the times.